ChemInform Abstract: Microwave‐Assisted Palladium‐Catalyzed Isonitrile Insertion in 2‐Bromophenylureas for Efficient Synthesis of 4‐Substituted Imino 4H‐Benzo[d][1, 3]oxazin‐2‐amines. Issue 34 (August 2015) - Pandey, Garima; Batra, Sanjay
Abstract The reaction tolerates aromatic and aliphatic 2‐bromophenylureas as well as aryl, alkyl, and sulfonyl group containing isocyanides.